Hedonistic Lifestyle and Income Level: Determining Factors in Student Financial Management - Siti Nginayah; Tri Maryani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
A hedonistic lifestyle is a social phenomenon that is increasingly prevalent among students, characterized by consumption patterns that are more oriented towards pleasure than long-term needs. This consumptive behavior can affect students' financial management, especially if it is not balanced with adequate financial literacy. This study aims to analyze the influence of hedonistic lifestyles and income levels on students' financial management behavior. This study uses a quantitative approach with a survey method of 100 students selected through purposive sampling techniques. Data were collected using a structured questionnaire that measures three main variables, namely hedonistic lifestyle, income level, and financial management behavior, with a Likert scale. Data analysis was carried out using multiple linear regression with the help of SPSS version 26 software. The results showed that a hedonistic lifestyle has a negative and significant effect on students' financial management behavior, while income level has a positive but insignificant effect. This indicates that although students with higher incomes have more financial resources, they do not necessarily have better financial management skills. These findings emphasize the importance of financial literacy in managing income and reducing the negative impacts of a consumptive lifestyle. This study provides implications for educational institutions to improve financial literacy programs to help students manage their finances wisely. In addition, the results of this study can be a reference for students to be more aware of the impact of lifestyle on their financial condition in the future.